THE EFFECT OF COMMUNICATION EFFECTIVENESS AND WORKING ENVIRONMENT CONDITIONS ON EMPLOYEE PRODUCTIVITY IN VOCATIONAL AND PRODUCTIVITY TRAINING CENTER (BBPVP) MEDAN - Dhea Rebeca Lbn. Raja; Adiwima Zebua; Davidly Manullang; Edward Alezandro Lbn. Raja (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study aims to test and analyze Communication on Employee Performance at the Medan Vocational Training and Productivity Center (BBPVP). To test and analyze the Work Environment on Employee Performance at the Medan Vocational Training and Productivity Center (BBPVP). To test and analyze Communication and work environment on Employee Performance at the Medan Vocational Training and Productivity Center (BBPVP). The location of the study was at the Medan City Vocational Training and Productivity Center (BBPVP) with a population of 120 employees and a sample of 54 people using proportional random sampling techniques. The number of samples taken in this study was 54 employees. This study uses a Likert Scale. The Likert scale is used to measure attitudes. The results of this study indicate that Based on the results of the analysis that has been discussed, it can be concluded that partially the Storytelling Marketing and Servicescape variables each have a positive and significant effect on the Interest in Visiting Air Soda Parbubu. In addition, simultaneously both variables have also been shown to have a positive and significant effect on the interest in visiting the destination.